2005
DOI: 10.1002/mrc.1586
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐substituted benzohydroxamic acids: 1H, 13C and 15N NMR spectra and NHOH proton exchange

Abstract: NMR spectra (1H, 13C, 15N) of para- and meta-substituted benzohydroxamic acids were studied in dry dimethyl sulfoxide solutions. The 13C chemical shifts were very close to those found by cross-polarization magic angle spinning in solids, the hydroxamic (not hydroximic) structure of which is unambiguous. The hydroxamic structure of these acids in DMSO solutions was proved independently by their 15N chemical shifts. The 15N and 1H chemical shifts of the NH-OH fragment showed excellent mutual dependences and depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…They conluded that (Z)-tert-butyldimethylsilyl-N-tertbutyldimethylsilyloxybenzoimidate, (Z)-tert-butyldiphenylsilyl-N-tert-butyl-diphenylsilyloxybenzoimidate, and N-tertbutyldiphenylsilyloxybenzoimidic acid possess hydroximic structures. [213]. For a series of substituted benzohydroxamic acids, the 15 N chemical shifts ranged from 162.7 to 170.7 ppm, indicating that in DMSO solution all compounds were present in the hydroxamic form Fig.…”
Section: Hydrogen Bonding and Prototropic Tautomerismmentioning
confidence: 97%
See 2 more Smart Citations
“…They conluded that (Z)-tert-butyldimethylsilyl-N-tertbutyldimethylsilyloxybenzoimidate, (Z)-tert-butyldiphenylsilyl-N-tert-butyl-diphenylsilyloxybenzoimidate, and N-tertbutyldiphenylsilyloxybenzoimidic acid possess hydroximic structures. [213]. For a series of substituted benzohydroxamic acids, the 15 N chemical shifts ranged from 162.7 to 170.7 ppm, indicating that in DMSO solution all compounds were present in the hydroxamic form Fig.…”
Section: Hydrogen Bonding and Prototropic Tautomerismmentioning
confidence: 97%
“…In order to obtain aromatic derivatives with a proton transferred to the nitrogen atom, the acidity of the OH group must be increased by appropriate substitution. Isomers of hydroxamic acids [213]. Furthermore, comparison of the contribution of the NH form in solution and in the solid state reveals that the NH form is more abundant in the solid state for the aromatic derivatives, although the extent varies greatly [152].…”
Section: Hydrogen Bonding and Prototropic Tautomerismmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, this is the first example observed for such type of exchange on a phenyl ring. However, the proton NH/OH exchange using 1 H, 13 C and 15 N NMR was previously observed [17]. Also, the NH/OH exchange as well as proton exchange is a familiar feature on metal centers [18][19][20].…”
Section: Ir and Nmr Studiesmentioning
confidence: 99%
“…The powerful biological activity of structurally heterogeneous hydroxamic acids is related to their ability to form stable chelates with a variety of metal ions [12,13]. Metal complexes of hydroxamic acids have also attracted considerable attention because of their tautomerisation [14] exhibiting hydroxamic or hydroximic acid forms. The theoretical and experimental studies have suggested that the hydroxamic form is prevalent in free acids [15] or metal hydroxamates [16].…”
Section: Introductionmentioning
confidence: 99%